THE MODERATING EFFECTS OF GENDER, CAREER, MORAL MINDSET ON THE RELATIONSHIP BETWEEN THE GRADUATE ATTRIBUTES AND READINESS FOR EMPLOYABILITY AMONG ENGINEERING COLLEGES GRADUATES IN OMAN - Hinai, Masoud Rashid Al; Bhuiyan, Abul Bashar; Husin, Nor Azilah (International Journal of Accounting & Finance Review, 2020)
The Omani higher education system has enlarged noticeably since 1970 both in the number of students and in the infrastructure.  As a result, there has been a wide investment to provide quality higher educational institutes capable of providing suitable graduates to fulfill the requirements of both public and private sectors with a focus on females to assure equal gender educational and career opportunities chances. Therefore, graduates’ readiness for employability has become a major issue for Higher Education Institutes (HEIs) in Oman due to the growing concern from governments and industries on the quality of the graduates.  Therefore, the main objective of the current study is to develop a conceptual framework for the graduate readiness for employability and incorporates the graduate attributes including human capital attributes, social capital attributes, individual attributes, institution-related attributes, and active learning attributes moderated by gender, career, and moral mindset among Engineering Graduate in Oman. The study uses available sources of existing literature based on the four main keywords ‘higher education’, ‘graduate attributes ‘or ‘readiness for employability, and ‘skills gaps in Oman’. The study also justified by the following theories which are human capital; education and economy development; behavior theory; and motivation theory. The literature utilized for this study covers the latest literature (from 2013 to 2020) extracted from Google Scholar, ProQuest, and Scopus, and other online resources. Based on the summary findings, the study develops a framework that analyses the effects of influential factors on the graduate readiness for employability that will be considered as an empirical study on the graduates of the engineering colleges in Oman. Moreover, the study also concluded that there are moderating effects of gender, moral mindset, and career mindset on the influence factors and the graduate readiness for employability among Omani engineering colleges’ students. The results of the study will fill the gap in understanding the main factors affecting the attainment of graduates’ readiness for employability skills in Oman. The study recommends justifying this conceptual framework by empirical data from the Engineering Graduate in the Higher Education Institutes (HEIs) and draw a policy guideline for ensuring of readiness of engineering graduates for employability in the HEIs in Oman.